GREEN PRODUCT, CONSUMER ATTITUDE, ENVIRONMENTAL AWARENESS IN PURCHASE INTENTION NPURE TONER - Luh Willa Yasmira Dewi; Putu Saroyini Piartrini (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Climate change and rising public concern for environmental issues have reshaped consumer behavior toward more environmentally friendly products, including in the beauty industry. NPure, an Indonesian local skincare brand built on the concept of green beauty, faces the challenge of strengthening consumer purchase intention amid lingering skepticism toward the authenticity of green products. This study analyzes the influence of green product and consumer attitude on purchase intention, and examines environmental awareness as a moderating variable for NPure toner in Denpasar, Bali. A quantitative survey was distributed to 130 NPure consumers selected through purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that green product and consumer attitude each have a positive and significant effect on purchase intention, while environmental awareness fails to moderate either relationship. These findings suggest that consumers' environmental awareness neither strengthens nor weakens the link between green product, attitude, and purchase intention toward NPure. The study concludes that green product quality and favorable consumer attitude are the primary drivers of purchase intention for environmentally friendly skincare, and recommends that future research test alternative moderators such as green trust or green perceived value.